Movement factors that improve dancing expression - Madrigal Huezo, Tania (2021)
This article develops a theoretical and historical analysis concerning the need to apply what Rudolf Von Laban proposed with respect to dance as a fundamental artistic expression for humanity and as a means for strengthening the expressive demands of dancers. The methodology employed consisted of bibliographic review combined with practical experiences as professor of Dramatic Art techniques at the National University of Costa Rica. In addition, a discussion on the contributions of Laban (1975) is developed; especially with respect to his notion in the teaching of dancing it has been introduced a new understanding of the elements of movement based upon modern research. The basic idea in the acquisition of the new dance, as in all forms of human physical activity, consists in a series of movements in which a certain effort is required and is specific to each of them; each action consist of a combination of effort elements which are derived from the attitudes and characteristics of each person towards a certain movement: Weight, Space, Time and Flow. Based upon the above, this work intends to examine with theoretical foundations the need to apply Laban´s proposals to strengthen the expressive competencies of the dance interpreter.